ECO-PESANTREN ASSESSMENT STUDY OF ISLAMIC BOARDING SCHOOL IN BANDA ACEH, INDONESIA - Bakri, Maysarah (Journal of Islamic Architecture, 2021)
The implementation of Eco-Pesantren is a contribution of the Islamic Architecture product towards the current global issue. Eco-Pesantren aims to produce a green Islamic boarding school, which contributes a positive effect in terms of environmental conservation and energy saving. Therefore, this research assesses the Eco-Pesantren implementation of Darul Ulum Islamic Boarding School in Banda Aceh. The research method is descriptive qualitative. The researcher collects data through in-situ observation based on the research tool. The result shows that this Islamic Boarding School is not yet categorized as an Eco-Pesantren. to implement this concept. The management should improve some aspects such as optimizing natural renewable resources, optimizing the existing green space, and optimizing waste management. This study also reveals the role of architects in implementing the Eco-building concept and determines the building performance.